Planning for Heterogeneous IoT with Time Guaranties - Cecílio, José (2017)
Distributed IoT Systems with time guaranties need to be carefully dimensioned to provide correct operations timings. In heterogeneous systems, with wired and wireless components, there are many factors that have implications regarding timings. Beside of developing real-time operating systems, IoT platforms for real-time communications need to be carefully dimensioned to provide correct operation timings. In this paper we propose a planning algorithm that allows building a heterogeneous IoT system to operate with timing constrains. Current solutions to plan and predict latencies in distributed IoT systems are currently mostly based on a set of rules-of-thumb. Since time division multiple access (TDMA), token-ring and Carrier Sense Multiple Access (CSMA) based medium access control protocols can coexist in the same network, new approaches are needed to work with any of these protocols and heterogeneity. We consider protocols used in industry-strength solutions and propose a latency model, which can be used by the engineering teams to guarantee strict timing compliance in their heterogeneous plans.